2012
DOI: 10.1111/j.1600-0781.2012.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric photosensitivity

Abstract: Summary Photosensitivity is a rarely encountered problem in the pediatric population. It may be caused by a diverse group of primary, idiopathic photosensitivity conditions, or may reflect photoexacerbation of an existing dermatosis. In addition, there are several genodermatoses, metabolic disorders, and connective tissue disorders that can present with photosensitivity, usually in addition to other extracutaneous clinical and laboratory findings. It is important that both dermatologic and pediatric practition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 34 publications
0
18
0
2
Order By: Relevance
“…O choro associado à exposição solar pode ser a única manifestação em idades precoces. 28 A sensação de queimadura acompanha-se de eritema e edema difusos das áreas expostas que podem evoluir para lesões de urticária, purpúra e equimoses. As lesões vesiculares ou bolhosas são raras.…”
Section: Protoporfiria Eritropoiéticaunclassified
See 1 more Smart Citation
“…O choro associado à exposição solar pode ser a única manifestação em idades precoces. 28 A sensação de queimadura acompanha-se de eritema e edema difusos das áreas expostas que podem evoluir para lesões de urticária, purpúra e equimoses. As lesões vesiculares ou bolhosas são raras.…”
Section: Protoporfiria Eritropoiéticaunclassified
“…A doença colestática e a insuficiência hepática, complicações mais graves, ocorrem em menos de 5% dos casos embora alguns deles tenham necessidade de transplante hepático. 28,30 O diagnóstico diferencial desta fotossensibilidade que ocorre minutos após a exposição solar é feito com a urticária solar e a síndrome de Smith-Lemli-Opitz (síndrome polimalformativa resultante de um défice metabólico da biossíntese do colesterol caracterizado por dismorfias craniofaciais, anomalias congénitas de vários órgãos, restrição de crescimento intra-uterino, alterações comportamentais e défice cognitivo).…”
Section: Protoporfiria Eritropoiéticaunclassified
“…following ultraviolet (UV) A or B light exposure, and pruritus is a key accompanying symptom of the eruption. Juvenile spring eruption (JSE), so named due to its nearly exclusive occurrence in children and predilection for onset in the spring, is considered by many experts to be a variant of PMLE [3,14]. Laboratory workup will show negative autoimmune lupus serologies and porphyrin studies, but it need not be performed in straightforward cases.…”
Section: Key Pointsmentioning
confidence: 99%
“…This may refer to the development of a new rash, aggravation of an existing dermatosis, or the experience of subjective symptoms of pruritus or paresthesias following exposure to sunlight or an artificial light source [2]. A diverse group of conditions may cause photosensitivity, and several such disorders can present at an early age, whereas others may preferentially affect the pediatric population [3][4]. In one of the largest studies examining the epidemiology of photosensitivity, over 25% of cases were reported to begin at or before 15 years of age [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation